ANALYSIS OF NUTRIENT CONTENT OF MAGGOT COMPOST (BSF FRASS) FROM PALM KERNEL MEALS (PKM) AND CASSAVA WASTE (CW) CONVERTED BY HERMETIA ILLUCENS LARVAE (DIPTERA: STRATIOMYIDAE) - Fitrianti, Elliza
Agro-industrial waste such as palm kernel meals (PKM) and cassava waste (CW) is often a serious environmental problem. However, the waste is often used for other purposes such as feed for ruminants and poultry. In addition, the rest of the waste treatment process can be used as compost or planting media. Since the last three decades, the Black Soldier Fly (BSF) or Hermetia illucens (Diptera Stratiomyidae) has been widely studied and used as an insect for treating organic waste. The purpose of this study is to determine the nutrient content of maggot compost (BSF Frass) from the bioconversion of palm kernel meals (PKM), cassava waste (CW), and commercial chicken feed (CCF) used as control by H. illucens larvae and their effect on the physical properties of the H. illucens larvae. soil. PKM and CW used as feed were fermented with EM4 for 7 days. A total of one hundred (100) 7-day-old BSF larvae were fed 2 types of waste in plastic containers, and each treatment was carried out 6 repetitions. The results showed that cassava from BIS had the highest nutrient content with a composition of 31.28% C; C/N ratio 18; 1.76% N; 0.95% P; 0.9% K; 0.23% Mg; 3165 ppm Fe; and 46 ppm Zn. Based on the results of this study, BSF Frass of PKM has the best nutrient content; and the provision of BIS cassava increases the best soil physical properties on bulk density and soil porosity parameters, increases soil organic matter so that the soil color becomes darker but does not significantly affect soil texture and consistency.